The European powers in the First World War an encyclopedia - Tucker, Spencer 1937-; Wood, Laura Matysek; Murphy, Justin D. (Garland reference library of the humanities, 1999)
Focuses on a great watershed event : The First World War was one of the great watershed events of the 20th century, not only costing millions of live but also disrupting existing social order, precipitating dramatic changes in the methods of waging warfare, and teaching victors new lessons about the treatment of vanquished foes. Provides valuable perspective : Now a new reference work helps to put this momentous historical milestone in perspective. Designed as a companion to Garland's The United States in the First World War, this new encyclopedia concentrates on non-U.S. aspects of the conflict. Its more than 600 alphabetically arranged, detailed entries offer information and insights on such topics as the perceived and underlying causes of war, diplomatic efforts to stop the slaughter, the shortsighted and ultimately disastrous peace terms, and a host of other subjects vital to a full understanding of the events. The Encyclopedia covers all major campaigns and battles,surveys weapons and devices of war, and examines the roles played in the events by statesmen, politicians, religious and military leaders, and prominent citizens. Covers key participants and concerns: Also included are biographies of individuals profoundly affected by the war who played major roles in history, such as De Gaule, Hitler, appraisals of military medicine, infantry tactics, the use of artillery, naval blockades, and other subjects; and surveys of such diverse topics as art, literature, and music in the war, camouflage, censorship, propaganda, the creation of Yugoslavia, the Jewish Legion, codebreaking, women in the war, and much more. Each entry is followed by a bibliography for pursuing inquires in depth and a subject index provides easy access.